Comparative analysis of contemporary remote sensing techniques and species distribution modelling in predicting spatial distribution of coastal habitats - Louise Forsblom; Ari-Pekka Jokinen; Dimitry Van der Zande; Mihailo Azhar; Dimitar Berov; Jacob Carstensen; Vivi Drakopoulou; Vasilis Gerakaris; Hege Gundersen; Jonne Kotta; Valeria Mobilia; Nadia Papadopoulou; et al. (Remote Sensing of Environment, 2026)

Assessment of Bottom Trawl Impacts on the Status of Seabed Communities in European Seas - Jan Geert Hiddink; Sebastian Valanko; Luke Batts; Esther D. Beukhof; Mats Blomqvist; Stefan Bolam; Belén Calero; Michele Casini; Marina Delgado; Jochen Depestele; Joanna Desmidt; Gabriele Di Bona; et al. (Fish and Fisheries, 2026)
Bottom trawling affects seabed habitats, but its large‐scale impacts remain poorly quantified. Assessment of trawling impacts is essential to support monitoring and achieving sustainability objectives under international conventions, sustainable development goals, and seafood certification programs. We present a Europe‐wide quantitative assessment of bottom trawling impacts, accounting for regional seabed‐community sensitivity drivers, across the Baltic, Atlantic, Mediterranean and Black Sea continental shelves. Using two risk‐based indicators of seabed status—Relative Benthic Status determined as benthic community biomass relative to seabed fauna carrying capacity (RBS tot ) and RBS sen (biomass of the 10% most sensitive fauna relative to carrying capacity)—we found substantial regional and habitat differences. The Black, Baltic and Aegean‐Levantine Seas showed low trawling intensity and high seabed status across habitats. In contrast, the Western Mediterranean, Ionian and Central Mediterranean and Adriatic Seas were the most severely impacted. Trawling affected the sensitive species biomass fraction more strongly than the total community biomass. RBS tot was in good condition (here chosen as RBS > 75% for epifauna) for over 79% of habitat‐ecoregion combinations. In contrast, RBS sen met this threshold in only 46% of these. A strong correlation emerged between the mean trawling intensity and RBS tot and RBS sen , allowing the use of SAR to estimate ecosystem status. This relationship can support decisions on where, and by how much, SAR reductions are needed to achieve good environmental status in regions where no detailed assessment is available. Our approach provides a quantitative framework to balance fishery production with ecosystem sustainability, offering tools for environmental and fisheries management in Europe.

CoDeMap: a classification scheme for benthic habitats from the coast to the deep sea in the Mediterranean and Black Sea - Valentina Grande; Lorenzo Angeletti; Mariacristina Prampolini; Giorgio Castellan; Giacomo Dalla Valle; Simonetta Fraschetti; Daniela Basso; Dimitar Berov; Valentina A. Bracchi; Frine Cardone; Giovanni Chimienti; Annalisa Falace; et al. (Frontiers in Marine Science, 2025)
The spatial representation of benthic habitats is essential across various applications, such as biodiversity monitoring, ecosystem management and conservation, and maritime spatial planning. In this context, classification schemes provide a universally understandable framework to characterize and chart the seafloor. This work introduces the Coast to Deep Mapping (CoDeMap) classification scheme for benthic habitats from the coast to the deep-sea environments. It consists of three main components (Morphology, Substrate and Biology) and it is conceived as a practical tool for users from various backgrounds who need to organize and interpret marine observational data, as well as characterize and map seafloors. While primarily developed for the Mediterranean Sea and the Black Sea, CoDeMap serves as a foundational framework that can be adapted to address any current or future similar request worldwide.

Deficiencies in monitoring practices of marine protected areas in southern European seas - Sylvaine Giakoumi; Katie Hogg; Manfredi Di Lorenzo; Nicolas Compain; Claudia Scianna; Giacomo Milisenda; Joachim Claudet; Dimitrios Damalas; Pierluigi Carbonara; Francesco Colloca; Athanasios Evangelopoulos; Igor Isajlović; et al. (Journal of Environmental Management, 2024)

The Status of Coastal Benthic Ecosystems in the Mediterranean Sea: Evidence From Ecological Indicators - Stanislao Bevilacqua; Stelios Katsanevakis; Fiorenza Micheli; Enric Sala; Gil Rilov; Gianluca Sarà; Dania Abdul Malak; Ameer Abdulla; Vasilis Gerovasileiou; Elena Gissi; Antonios D. Mazaris; Carlo Pipitone; et al. (Frontiers in Marine Science, 2020)

A Genome-Wide Approach to the Phylogeography of the Mussel Mytilus galloprovincialis in the Adriatic and the Black Seas - Marta Paterno; Levent Bat; Jamila Ben Souissi; Elisa Boscari; Aurore Chassanite; Leonardo Congiu; Giuseppe Guarnieri; Claudia Kruschel; Vesna Mačić; Ilaria Anna Maria Marino; Dragos Micu; Nataliya Milchakova; et al. (Frontiers in Marine Science, 2019)

Light and Shade in Marine Conservation Across European and Contiguous Seas - Simonetta Fraschetti; Carlo Pipitone; Antonios D. Mazaris; Gil Rilov; Fabio Badalamenti; Stanislao Bevilacqua; Joachim Claudet; Hrvoje Carić; Karsten Dahl; Giovanni D’Anna; Darius Daunys; Matthew Frost; et al. (Frontiers in Marine Science, 2018)

New Mediterranean Biodiversity Records (July 2018) - NIKI CHARTOSIA; DIMITRIS ANASTASIADIS; HOCEIN BAZAIRI; FABIO CROCETTA; ALAN DEIDUN; MARIJA DESPALATOVIĆ; VINCENZO DI MARTINO; NIKOS DIMITRIOU; BRANKO DRAGIČEVIĆ; JAKOV DULČIĆ; FURKAN DURUCAN; DENIZ HASBEK; et al. (Mediterranean Marine Science, 2018)
In the present article, new records are given for 15 species (4 native and 9 alien and 2 cryptogenic), belonging to 6 Phyla (i.e. Chlorophyta, Ctenophora, Cnidaria, Mollusca, Arthropoda, and Chordata), from 10 Mediterranean countries: Morocco: the finding of the crab Callinectes sapidus represents the westernmost one of the species in the Mediterranean; Italy: first records of the nudibranch Polycera hedgpethi from the harbour of La Spezia, and first finding of the invasive ctenophore Mnemiopsis leidyi in the Fiora River; Tunisia: Caulerpa taxifolia var. distichophylla is recorded for the first time, showing an even wider distribution in the Mediterranean; Greece: the finding of the jellyfish Pelagia benovici represents the first record of the species in the Ionian Sea, while the finding of the smallscale codlet Bregmaceros nectabanus in the Ionian Sea is another interesting first report for the area; Malta: the cryptogenic scleractinian coral Oculina patagonica was recorded; Slovenia: the parasitic copepod Demoleus heptapus was recorded from a sixgill bluntnose shark, Hexanchus griseus; Croatia: the Lessepsian cephalaspidean mollusc Haminoea cyanomarginata is recorded for the first time from the area; Bulgaria: the Asian date mussel Arcuatula senhousia was recorded from the Black Sea; Cyprus: the Lessepsian gastropod Viriola sp. [cf. corrugata) was recorded for the first time from the area, while two decapod species were recorded also for the first time from Cyprus, i.e. the caridean shrimp Pasiphaea sivado and the anomuran Munida curvimana; Turkey: the acari Lohmannella falcata is recorded for the first time from Antalya and the Lessepsian fish Priacanthus sagittarius in the Levantine coasts of Turkey (off Hatay/Arsuz) showing that this species has extended its range in a very short time.

Estimation of net ecosystem metabolism of seagrass meadows in the coastal waters of the East Sea and Black Sea using the noninvasive eddy covariance technique - Jae Seong Lee; Dong-Jin Kang; Elitsa Hineva; Violeta Slabakova; Valentina Todorova; Jiyoung Park; Jin-Hyung Cho (Ocean Science Journal, 2017)